Carrier density dependence of 1/f noise in graphene explained as a result of the interplay between band-structure and inhomogeneities. (20th May 2016) - Pellegrini, B; Marconcini, P; Macucci, M; Fiori, G; Basso, G
Abstract: We present a model for 1/ f noise in graphene based on an analysis of the effect of charge trapping and detrapping events on the fluctuations of the number of charge carriers. Inclusion of a Gaussian distribution of fluctuations of the electrostatic potential enables us to reproduce all the various experimentally observed behaviors of the flicker noise power spectral density as a function of carrier density, both for monolayer and bilayer graphene. The key feature of a flicker noise minimum at the Dirac point that appears in bilayer graphene and sometimes also in monolayer graphene is explained in terms of the disappearance, when the number of electrons equals that of holes, of the carrier number fluctuations induced by trapping events. Such a disappearance is analyzed with two different approaches, in order to gain a better understanding of the physical origin of the effect, and to make some considerations about possible analogous phenomena in other semiconductors.